2010
DOI: 10.3109/10641960903254513
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Home Blood Pressure Measurement in the Morning in Patients with Type 2 Diabetes: Long-Term Results of a Prospective Longitudinal Study

Abstract: Previous cross-sectional studies have demonstrated that blood pressure measurements at home (HBP) in the morning display stronger predictive power for micro- and macrovascular complications in type 1 and 2 diabetic patients than casual/clinic blood pressure (CBP) measurements. This longitudinal study investigated which of these measurements offers stronger predictive power for outcomes over 6 years. At baseline, 400 Japanese patients with type 2 diabetes were classified as hypertensive or normotensive based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…Subjects comprised 400 Japanese patients with T2DM enrolled between 1999 and 2005 [3]. After a detailed *Address correspondence to this author at the Joetsu General Hospital, Joetsu, Niigata, 943-0502, Japan; Tel: +81-0258-36-3986; Fax: +81-0258-36-3986; E-mail: kkam-int@echigo.ne.jp baseline examination, subjects were followed up for allcause mortality and morbidity, and event of cancer.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjects comprised 400 Japanese patients with T2DM enrolled between 1999 and 2005 [3]. After a detailed *Address correspondence to this author at the Joetsu General Hospital, Joetsu, Niigata, 943-0502, Japan; Tel: +81-0258-36-3986; Fax: +81-0258-36-3986; E-mail: kkam-int@echigo.ne.jp baseline examination, subjects were followed up for allcause mortality and morbidity, and event of cancer.…”
Section: Subjectsmentioning
confidence: 99%
“…Baseline characteristics of participants have been described previously [3]. At beginning of the study, 329 patients (82%) were receiving treatment with oral hypoglycemic drugs and/or insulin regimens for hyperglycemia, 196 patients (49%) were receiving treatment with various antihypertensive drugs for HT, and no patient was receiving treatment for anemia [3,4].…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation was consistent with a previous study showing that morning BP was a stronger predictor for UAE than clinic BP. 15 It is interesting to note that morning SBP reduction was significantly correlated with UAE reduction even after adjustment for baseline UACR and other confounding factors (Figure 2). Moreover, the subgroup analysis showed that morning SBP reduction is an independent determinant of UAE reduction in both the combination regimen and high-dose regimen.…”
Section: Morning Sbp Reduction and Uae Reductionmentioning
confidence: 99%
“…while 3, 1, 1 and 1 patients in the CH group were due to cancer with brain, breast or pancreas, CVD, CHD and unknown cause, respectively, and 2 and 1 patients in the CN group were due to CVD and CHD, respectively (Kamoi et al, 2010). As shown in figure 7, new or worsened events of microvascular complications were observed in 72 patients (18%) included 36 with retinopathy and 59 with nephropathy, while improved events of microvascular complications were shown in 102 patients (25.5%) included 27 with retinopathy and 79 with nephropathy.…”
Section: Endpoints and Outcome Measuresmentioning
confidence: 99%